Palliative and Hospice Social Work Roles in the U.S. - Csikai, Ellen L. (Magyar Gerontológia, 2021)
Palliative care services worldwide continue to grow, primarily in response to a human rights approach and to respond to the aging of the population, increasing prevalence of chronic illnesses and cancer mortality. While there is recognition in the WHO definition of palliative care that not only physical, but also psychological, social and spiritual aspects of care must be part of services provided, how these are addressed varies greatly by country and region of the world.In the U.S., social work services are mandated to be provided by hospice organizations seeking funding from Medicare (governmental insurance for people over age 65) and supports the tenets of the palliative care philosophy to provide person-centered holistic care. The role of palliative and hospice social workers is highly aligned with the values of the profession centered on the dignity and worth of all humans and the commitment to improving quality of life throughout life and especially at the end of life. Older adults make up the overwhelming majority of hospice recipients in the U.S. and attention to their daily needs and those of the family caregivers is essential to maximize quality of life.This presentation will focus on the roles of social workers in the U.S., particularly with older adults, in various palliative care settings and how this may compare to roles across the globe.